KOMPETENSI KOMUNIKASI PENYULUH AGAMA HONORER DI KECAMATAN CIBINONG KABUPATEN BOGOR - M Taufik Hidayatullah (Harmoni, 2012)
This article focuses on explanation about the competency of The Volunteer Religious Educator. The research was conducted in November-Desember 2011 in Cibinong Subdistrict, Bogor Regency. The population were 27 Volunteer Religious Educator and 149 majelis taklim member under their guidance. Sampling process was by census procedure sampling for the Volunteer Religioous Educator and by random sampling for majelis taklim member. Data collection techniques were questionnaire, observation, in-depth interview, and documentary study. The statistical analysis used was descriptive and Tau-b Kendall correlation. The findings indicated that Volunteer Religious Educator had a high level in communication competency and several factors influenced their job motivation and communication competency.